COMPLEX ORTHODONTIC-IMPLANT TREATMENT IN INCISOR HYPODONTIA CASES - Miroslava Dinkova (Journal of IMAB, 2020)
Purpose:The purpose of the current paper is to show clinical cases with unilateral and bilateral incisal hypodontia, treated with complex orthodontic – implant treatment. Materials and methods: 3 representative clinical cases are included with interdisciplinary complex treatment protocol attached: case 1 – asymmetric upper right lateral incisor hypodontia, case 2 – symmetric upper lateral incisors hypodontia and case 3 – symmetric lower central incisor hypodontia. Cases are followed over ten and a half and eight years retention period. The interdisciplinary treatment protocol includes the following stages: First stage: Pretreatment preparation to form a crew, planning the type of the manipulations, sequence and duration, finance plan, discussion of the treatment plan and alternative options with the patient, signed informed consent. Second stage: Orthodontic treatment. Third stage: Implant restorations. Fourth stage: Aesthetic prosthetic restorations. Retention period. Results:In all three cases, aesthetics were improved. We obtained the correct ratio of the upper lip to the dental arch. Paralleling the roots of the frontal teeth and their levelling up provided correct, balanced occlusal and proximal contacts, which improved the function and provided stability of the treatment results. Conclusion:The complex orthodontic-implantology approach for the treatment of single tooth hypodontia the tooth arch is successful and ensures optimal and lasting restoration of function and aesthetics of the dental-jaw system.